Atypically presented flank pain in a patient with pulmonary embolism; a case report and literature review of a diagnostic dilemma - Mohammed Alra’e; Maaweya Jabareen; Hanan Qunibi; Saleh Juneidi; Wasef Alhroub; Walid Tamimi; Musad Shawar (Medicine, 2026)
Rationale: Pulmonary embolism (PE) is a potentially life-threatening condition with a broad spectrum of clinical presentations, making diagnosis challenging. Although dyspnea, pleuritic chest pain, and cough are common manifestations, atypical presentations may lead to delayed diagnosis and treatment. Patient concerns: We report the case of a 44-year-old woman who presented with acute right-sided flank pain as her predominant symptom, without evidence of urinary or gastrointestinal pathology. Diagnoses: Initial abdominal imaging was unremarkable, and laboratory investigations for urinary pathology were negative. Given her risk factors, including recent travel and oral contraceptive pill use, along with subtle chest findings, further evaluation was performed and revealed a right subsegmental PE with minimal pleural effusion. Interventions: Anticoagulation therapy was promptly initiated. Outcomes: The patient experienced complete resolution of her flank pain and other symptoms within 72 hours. Lessons: Abdominal pain associated with PE has been described in the literature; however, isolated flank pain is a rare presentation. Proposed mechanisms include diaphragmatic pleural irritation, pulmonary infarction, and referred pain through shared thoracic sensory pathways. This case highlights the importance of maintaining a high index of suspicion for PE in patients presenting with unexplained atypical pain, particularly when risk factors are present. Early recognition and treatment of atypical PE presentations may prevent diagnostic delays and reduce associated morbidity and mortality.